Estudo do potencial antitumoral do complexo de Rutênio (II) coordenado com alopurinol em células de carcinoma mamário - Travassos, Ingrid Oliveira (2017)
Introduction: Ruthenium-based metallo complexes have been established as antineoplasic compounds with excellent activity, greater selectivity and lower toxicity, being able to coordinate with several different ligands and acting in several biological targets. Objective: This study aims to evaluate the antineoplastic potential of Ruthenium (II) complexes coordinated with allopurinol in mammary carcinoma, Ehrlich ascites tumor, MDA-MB-231 and non-tumor L-929. Methodology: Complexes of Ruthenium (II) coordinated with allopurinol were denominated Complxo 1 [RuCl2(alo)2(PPh3)] and Complex 2 [RuCl2(alo)2(dppb)]. Complexes 1 and 2 and Allopurinol were evaluated and compared in relation to antiproliferative activity by the MTT method. Effects of complex 2 on cell cycle kinetics were evaluated in TAE cells as well as the cell death profile through the apoptosis assay by flow cytometry and fluorescence microscopy. To determine the interaction of complex 2 with DNA the comet assay was performed. The antimetastatic potential was determined by the long-term migration and cytotoxicity assay in MDA-MB-231 cells. The expression of apoptotic proteins was performed via Western blotting. Results and discussions: Complex 2 showed better antitumor activity against lineages tested compared to complex 1 and Allopurinol, being selected for other tests. Complex 2 was able to act on the cell cycle interrupting its progression in the G0 / G1 phase. It has been shown a strong interaction of complex 2 with DNA, being proved by the evaluation of the characteristics of cellular death triggered by complex 2. A possible antimetastatic potential in MDA-MB-231 cells was also observed. Conclusions: Therefore, this new Ruthenium (II) complex associated with allopurinol may be considered a promising compound for antitumor purposes, resulting from its peculiar apoptotic mechanism.